ANALISIS INTERAKSI GURU DAN SISWA DALAM PEMBELAJARAN IPAS DI KELAS V SDN 12 KOTO BARU - Ilham Asmaryadi, Ahmad; Eriswan Fitri, Trinindi; Pebrian Dini, Wilia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the fact that the interaction between teachers and students in science learning in several classes at SDN 12 Koto Baru has not been fully optimal, as seen from students who tend to be passive, less courageous in asking questions, the learning process is still dominated by one-way learning, and the use of technology in learning is still relatively rare. However, this condition is not universal, one of which is in grade V where the interaction is already good. This study aims to describe how the interaction occurs between teachers and students in science learning in grade V of SDN 12 Koto Baru. The research method used in this study is descriptive qualitative. Data collection techniques used are through observation, interviews, and documentation. Data analysis techniques use data reduction techniques, data presentation, and drawing conclusions. Data validity tests are through source triangulation, technical triangulation, and conducting member checks. The results of the study indicate that the interaction that occurs between teachers and students in science learning in grade V of SDN 12 Koto Baru is good. The form of interaction is an associative interaction that is shown by cooperation between students in doing assignments. The interaction patterns used by teachers are not limited to one-way, teacher-centered interactions that can lead to student boredom, but also include two-way, three-way, and multi-way interaction patterns. Equally important, the quality of these interactions is excellent, as evidenced by student engagement, effective communication, and the classroom learning atmosphere.